Penerapan Model Pembelajaran Koperatif Tipe Number Head Together Untuk Meningkatkan Hasil Belajar Siswa SD - Muh Idham Haliq; Irman Syarif; Nur Hikmah; M Yunus Sudirman (Universitas Muhammadiyah Enrekang, 2022)
Abstract: This study aims to improve student learning outcomes in class III UPT SDN 138 Kulinjang through the application of the NHT (Number Head Together) type of cooperative learning model. The collected student learning outcomes data were analyzed qualitatively. The results of this study indicate that the application of the NHT (Number Head Together) type of cooperative learning model can improve the learning outcomes of third grade students of UPT SDN 138 Kulinjang. This can be seen from the increase in student learning outcomes in the first cycle, the average score of students is 75.63 with a learning completeness percentage of 66.67% and the average value of students in the second cycle is 85.83 with a learning completeness percentage of 83.33%. Thus, there is an increase in student learning outcomes after applying the NHT (Number Head Together) learning model, so it can be concluded that the NHT (Number Head Together) learning model can improve student learning outcomes in subtheme 1 characteristics of living things in class III UPT SDN 138 Kulinjang, Enrekang Regency. Abstrak: Penelitian ini bertujuan untuk meningkatkan hasil belajar Peserta Didik di kelas III UPT SDN 138 Kulinjang melalui penerapan model pembelajaran kooperatif tipe NHT (Number Head Together). Data hasil belajar Peserta Didik yang terkumpul dianalisis secara kualitatif. Hasil penelitian ini menunjukkan bahwa penerapan model pembelajaran kooperatif tipe NHT (Number Head Together) dapat meningkatkan hasil belajar Peserta Didik kelas III UPT SDN 138 Kulinjang. Hal ini dapat dilihat dari peningkatan hasil belajar Peserta Didik pada siklus I nilai rata-rata Peserta Didik 75,63 dengan persentase ketuntasan belajar 66,67% dan nilai rata Peserta Didik pada siklus II 85,83 dengan persentase ketuntasan belajar 83,33%. Dengan demikian, terdapat peningkatan hasil belajar Peserta Didik setelah menerapkan model pembelajaran NHT (Number Head Together), sehingga dapat disimpulkan bahwa model pembelajaran NHT (Number Head Together) dapat meningkatkan hasil belajar Peserta Didik pada subtema 1 ciri-ciri makhluk hidup di kelas III UPT SDN 138 Kulinjang Kabupaten Enrekang.